1992
DOI: 10.1121/1.402776
|View full text |Cite
|
Sign up to set email alerts
|

Frequency dependence of binaural performance in listeners with impaired binaural hearing

Abstract: Binaural performance was measured as a function of stimulus frequency for four impaired listeners, each with bilaterally symmetric audiograms. The subjects had various degrees and configurations of audiometric losses: two had high-frequency, sensorineural losses; one had a flat sensorineural loss; and one had multiple sclerosis with normal audiometric thresholds. Just noticeable differences (jnd's) in interaural time, interaural intensity, and interaural correlation as well as detection thresholds for NoSo and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
69
2

Year Published

1998
1998
2021
2021

Publication Types

Select...
5
3
2

Relationship

0
10

Authors

Journals

citations
Cited by 64 publications
(77 citation statements)
references
References 0 publications
6
69
2
Order By: Relevance
“…However, the group difference was not significant for the resulting BMLDs (500 Hz: p ¼ 0.276, 1 kHz: p ¼ 0.066, mean: p ¼ 0.120, two-sample t-tests), and most HI listeners obtained BMLDs within the NH range. This is consistent with earlier reports of BMLDs (Staffel et al, 1990;Gabriel et al, 1992;Strelcyk and Dau, 2009), in which HI listeners showed elevated thresholds in both the diotic and dichotic conditions, leading to less pronounced differences with NH listeners in terms of masking release.…”
Section: Binaural Masking Release a Binaural Masking Level Diffsupporting
confidence: 82%
“…However, the group difference was not significant for the resulting BMLDs (500 Hz: p ¼ 0.276, 1 kHz: p ¼ 0.066, mean: p ¼ 0.120, two-sample t-tests), and most HI listeners obtained BMLDs within the NH range. This is consistent with earlier reports of BMLDs (Staffel et al, 1990;Gabriel et al, 1992;Strelcyk and Dau, 2009), in which HI listeners showed elevated thresholds in both the diotic and dichotic conditions, leading to less pronounced differences with NH listeners in terms of masking release.…”
Section: Binaural Masking Release a Binaural Masking Level Diffsupporting
confidence: 82%
“…This fine structure evokes phaselocked activity, i.e., synchronized timing of action potentials, in the subsequent stages of neural processing. Deficits in TFS processing have been found in some earlier studies on, e.g., pure-tone frequency discrimination (e.g., Turner and Nelson, 1982;Freyman and Nelson, 1991), low-rate frequency-modulation detection (e.g., Zurek and Formby, 1981;Moore and Skrodzka, 2002;Buss et al, 2004;) and binaural masked detection (e.g., Hall et al, 1984;Gabriel et al, 1992). Also, several studies suggested a relation between ageing and deficits in TFS processing as well as speech reception (e.g., Pichora-Fuller and Schneider, 1992;Strouse et al, 1998;Schneider et al, 2002;Ross et al, 2007;Hopkins et al, 2008;).…”
Section: Introductionmentioning
confidence: 92%
“…Koehnke, Culotta, Hawley,and Colburn (1995), who studied II listeners with sensorineural hearing loss, noted that most, but not all, of these listeners had smaller MLDs at 500 Hz. Gabriel, Koehnke, and Colburn (1992) Figure 3. Decibel increase in dichotic threshold as a function of the amount ofIAA for the younger and older subjects in the present study, and for the subjects in the study of Colburn and Latimer (1978), who were tested in dichotic conditions nearly identical to ours (see note 3).…”
Section: General Discussion and Conclusionmentioning
confidence: 99%